Identification of the Paleocene-Eocene boundary in coastal strata in the Otway Basin, Victoria, Australia - Frieling, Joost; Pross, Jörg (Journal of micropalaeontology, 2018)
Abstract. Detailed, stratigraphically well-constrained environmental reconstructions are available for Paleocene and Eocene strata at a range of sites in the southwest Pacific Ocean (New Zealand and East Tasman Plateau; ETP) and Integrated Ocean Discovery Program (IODP) Site U1356 in the south of the Australo-Antarctic Gulf (AAG). These reconstructions have revealed a large discrepancy between temperature proxy data and climate models in this region, suggesting a crucial error in model, proxy data or both. To resolve the origin of this discrepancy, detailed reconstructions are needed from both sides of the Tasmanian Gateway. Paleocene-Eocene sedimentary archives from the west of the Tasmanian Gateway have unfortunately remained scarce (only IODP Site U1356), and no well-dated successions are available for the northern sector of the AAG. Here we present new stratigraphic data for upper Paleocene and lower Eocene strata from the Otway Basin, southeast Australia, on the (north)west side of the Tasmanian Gateway. We analyzed sediments recovered from exploration drilling (Latrobe-1 drill core) and outcrop sampling (Point Margaret) and performed high-resolution carbon isotope geochemistry of bulk organic matter and dinoflagellate cyst (dinocyst) and pollen biostratigraphy on sediments from the regional lithostratigraphic units, including the Pebble Point Formation, Pember Mudstone and Dilwyn Formation. Pollen and dinocyst assemblages are assigned to previously established Australian pollen and dinocyst zonations and tied to available zonations for the SW Pacific. Based on our dinocyst stratigraphy and previously published planktic foraminifer biostratigraphy, the Pebble Point Formation at Point Margaret is dated to the latest Paleocene. The globally synchronous negative carbon isotope excursion that marks the Paleocene-Eocene boundary is identified within the top part of the Pember Mudstone in the Latrobe-1 borehole and at Point Margaret. However, the high abundances of the dinocyst Apectodinium prior to this negative carbon isotope excursion prohibit a direct correlation of this regional bio-event with the quasi-global Apectodinium acme at the Paleocene-Eocene Thermal Maximum (PETM; 56Ma). Therefore, the first occurrence of the pollen species Spinizonocolpites prominatus and the dinocyst species Florentinia reichartii are here designated as regional markers for the PETM. In the Latrobe-1 drill core, dinocyst biostratigraphy further indicates that the early Eocene (∼56-51Ma) sediments are truncated by a ∼10Myr long hiatus overlain by middle Eocene (∼40Ma) strata. These sedimentary archives from southeast Australia may prove key in resolving the model-data discrepancy in this region, and the new stratigraphic data presented here allow for detailed comparisons between paleoclimate records on both sides of the Tasmanian Gateway.
Gesehen am 25.07.2019